Intraspecific Transcriptome Variation and Sex-Biased Expression in Anopheles arabiensis. (25th August 2021) - Jayaswal, Vivek; Ndo, Cyrille; Ma, Hsiu-Ching; Clifton, Bryan D; Pombi, Marco; Cabrera, Kevin; Couhet, Anna; Mouline, Karine; Diabaté, Abdoulaye; Dabiré, Roch; Ayala, Diego; Ranz, José M
Abstract: The magnitude and functional patterns of intraspecific transcriptional variation in the anophelines, including those of sex-biased genes underlying sex-specific traits relevant for malaria transmission, remain understudied. As a result, how changes in expression levels drive adaptation in these species is poorly understood. We sequenced the female, male, and larval transcriptomes of three populations of Anopheles arabiensis from Burkina Faso. One-third of the genes were differentially expressed between populations, often involving insecticide resistance-related genes in a sample type-specific manner, and with the females showing the largest number of differentially expressed genes. At the genomic level, the X chromosome appears depleted of differentially expressed genes compared with the autosomes, chromosomes harboring inversions do not exhibit evidence for enrichment of such genes, and genes that are top contributors to functional enrichment patterns of population differentiation tend to be clustered in the genome. Further, the magnitude of variation for the sex expression ratio across populations did not substantially differ between male- and female-biased genes, except for some populations in which male-limited expressed genes showed more variation than their female counterparts. In fact, female-biased genes exhibited a larger level of interpopulation variation than male-biased genes, both when assayed in males and females. Beyond uncovering the extensive adaptive potential of transcriptional variation in An. Arabiensis, our findings suggest that the evolutionary rate of changes in expression levels on the X chromosome exceeds that on the autosomes, while pointing to female-biased genes as the most variable component of the An. Arabiensis transcriptome.